Treatment of cryptorchidism in pediatric surgical practice: a multicenter study - M. A. Axelrov; S. V. Minaev; M. P. Razin; Sh. A. Yusupov; N. A. Tsap; V. A. Tarakanov; J. A. Shamsiev; I. Yu. Karpova; M. M. Smolentsev; T. V. Sergienko; M. A. Baturov; E. S. Daniyarov; et al. (Вестник урологии, 2023)
Introduction. Cryptorchidism is a common disease in pediatric urological and andrological practice since the issues of tactical approaches and its optimal treatment remain extremely relevant. Cryptorchidism makes a significant contribution to the structure of male infertility.Objective. To conduct a retrospective analysis of treatment results in children and adolescents with cryptorchidism.Materials & methods. This study summarises the treatment results of 8308 patients with cryptorchidism aged from 6 months to 17 years who underwent inpatient treatment in the Russian Federation and the Republic of Uzbekistan.Results. It was revealed that from 2015 to 2019, patients were admitted for surgical treatment evenly over the years. The ratio of right-sided / left-sided / bilateral cryptorchidism was 4.6 : 4.4 : 1 The inguinal form prevailed more than 6 times over the abdominal location. At the same time, 26.1% of the patients underwent surgery at the optimal time, and 9.8% were older than 10 years. More often, children are operated from an open inguinal access (95.0%), much less often — laparoscopically and percutaneously. Stage-by-stage treatment was carried out in 6.0% of patients.Conclusion. Thus, the approach presented in the study in the surgical treatment of cryptorchidism provided good treatment results. The number of disease relapses was 1.9% (mainly among children over 7 years old). Most surgeons are very reserved about primary orchidectomies (only 3.8% were performed).